Does temperature constrain diet choice in a marine herbivorous fish? - Johnson, JS; Raubenheimer, D; Bury, SJ; Clements. KD (Springer, 2020)
The temperature constraint hypothesis (TCH) states that low water temperatures constrain the efficiency of algal digestion in fishes to an extent that limits the viability of herbivory. It is a widely cited explanation for the decline in diversity and abundance of marine herbivorous fishes at high latitudes. A key prediction of this hypothesis is that temperature-related physiological constraints may be ameliorated in free-living herbivores by a shift from herbivory to omnivory. We investigated this prediction by examining the diet of the primarily herbivorous marine fish Odax pullus (Labridae) at multiple locations spanning a gradient of 10° latitude and encompassing a change in median annual sea surface temperature of 5–7 °C. Foregut content and stable isotope analyses were used to compare diet across locations and results were evaluated against the prediction that a latitudinal temperature constraint on herbivory would result in significant variation in the composition of adult diets or the timing of an ontogenetic switch from omnivory to herbivory at colder, higher latitudes. We found that neither the proportion of animal material consumed nor ontogenetic changes in diet varied across the distributional range of this species in a manner consistent with the predictions of the TCH. This study demonstrates that water temperature does not constrain herbivory in a marine ectothermic herbivore and thus challenges a widely cited hypothesis.